Differential kinetic dynamics and heating of ions in the turbulent solar wind. (2nd December 2016) - Valentini, F; Perrone, D; Stabile, S; Pezzi, O; Servidio, S; Marco, R De; Marcucci, F; Bruno, R; Lavraud, B; Keyser, J De; Consolini, G; Brienza, D; et al.
Abstract: The solar wind plasma is a fully ionized and turbulent gas ejected by the outer layers of the solar corona at very high speed, mainly composed by protons and electrons, with a small percentage of helium nuclei and a significantly lower abundance of heavier ions. Since particle collisions are practically negligible, the solar wind is typically not in a state of thermodynamic equilibrium. Such a complex system must be described through self-consistent and fully nonlinear models, taking into account its multi-species composition and turbulence. We use a kinetic hybrid Vlasov–Maxwell numerical code to reproduce the turbulent energy cascade down to ion kinetic scales, in typical conditions of the uncontaminated solar wind plasma, with the aim of exploring the differential kinetic dynamics of the dominant ion species, namely protons and alpha particles. We show that the response of different species to the fluctuating electromagnetic fields is different. In particular, a significant differential heating of alphas with respect to protons is observed. Interestingly, the preferential heating process occurs in spatial regions nearby the peaks of ion vorticity and where strong deviations from thermodynamic equilibrium are recovered. Moreover, by feeding a simulator of a top-hat ion spectrometer with the output of the kinetic simulations, we show that measurements by such spectrometer planned on board the Turbulence Heating ObserveR (THOR mission), a candidate for the next M4 space mission of the European Space Agency, can provide detailed three-dimensional ion velocity distributions, highlighting important non-Maxwellian features. These results support the idea that future space missions will allow a deeper understanding of the physics of the interplanetary medium.